The Contribution of Digital Health in the Response to Covid-19 in Vietnam - Long Viet Bui; Son Thai Ha; Ha Ngoc Nguyen; Truong Thanh Nguyen; Thuy Phuong Nguyen; Kien Tran; Tuyen Van Tran; Tu Huu Nguyen; Thong Huy Tran; Nghiem Duc Pham; Hanh My Bui; Hanh My Bui (Frontiers Media S.A., 2021)
Emerging from early of 2020, the COVID-19 pandemic has become one of the most serious health crisis globally. In response to such threat, a wide range of digital health applications has been deployed in Vietnam to strengthen surveillance, risk communication, diagnosis, and treatment of COVID-19. Digital health has brought enormous benefits to the fight against COVID-19, however, numerous constrains in digital health application remain. Lack of strong governance of digital health development and deployment; insufficient infrastructure and staff capacity for digital health application are among the main drawbacks. Despite several outstanding problems, digital health is expected to contribute to reducing the spread, improving the effectiveness of pandemic control, and adding to the dramatic transformation of the health system the post-COVID era.